2016
DOI: 10.1002/ptr.5652
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Essential Oils Focusing on Diterpenes

Abstract: Among all plant derivates, essential oils (EOs) have gained the attention of many scientists. Diterpenes, a family of components present in some EO, are becoming a milestone in the EOs world. The goal of this review is to describe a scenario of diterpenes taking into health-consumption deportment. Previous studies revealed that diterpenes have antioxidant, antimicrobial, antiviral, antiprotozoal, cytotoxic, anticancer, antigenotoxic, antimutagenic, chemopreventive, antiinflammatory, antinociceptive, immunostim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 227 publications
0
67
0
Order By: Relevance
“…25 It has suggested that reducing viral load and cytokines levels by therapy, could prevent or lessen the chances of patients progressing to severe disease. 3,4 Owing to their antiviral and anti-inflammatory properties, [17][18][19] terpenes could have strong potential for being used in the search of new drugs for dengue. This study aimed to evaluate the antiviral activity in vitro of compounds found in essential oils with anti-dengue activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 It has suggested that reducing viral load and cytokines levels by therapy, could prevent or lessen the chances of patients progressing to severe disease. 3,4 Owing to their antiviral and anti-inflammatory properties, [17][18][19] terpenes could have strong potential for being used in the search of new drugs for dengue. This study aimed to evaluate the antiviral activity in vitro of compounds found in essential oils with anti-dengue activity.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest on these compounds because of their antimicrobial, antitumoral and anti-inflammatory properties. 17,18,19 Thus, terpenes and terpenoids offer a great opportunity to find novel lead molecules with specific inhibitory mechanisms on DENV. Antiviral activity of terpenes against Flavivirus have been demonstrated: citral blocked the Yellow-Fever Virus replication in vitro, 15 and treatment with combined monoterpenes delayed morbidity of mice due to West Nile Virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…According to Islam et al (2016a), about 25% pharmaceutically consumed drugs are derived from natural origins. Plants are the potential sources in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of medicinal plants in the modern medicines is vast and increasing day by day. It is due to the presence of abundant phytochemicals in a small amount of plant sample (Rao and Arora 2014; Islam et al 2016a). This study aimed to evaluate an antipyretic, analgesic and anti-inflammatory activity of the meth- …”
Section: Introductionmentioning
confidence: 99%